Layered Authentication Optimization in IoT-Based Package Receiving System using Voice-Trigger and PIN Verification - Mulia Sulistiyono; Muhtar Efendi; Uyock Anggoro Saputro; Bernadhed Bernadhed (Journal of Applied Informatics and Computing, 2026)
The rapid growth of courier and e-commerce services has increased the risk of package delivery problems, including unattended deliveries, package theft, and fraudulent claims by unauthorized recipients. To address these issues, this paper proposes the design and implementation of an Internet of Things (IoT)–based package receiving system that integrates voice recognition, PIN-based authentication, and remote monitoring capabilities. The proposed system employs a voice recognition module as an initial access trigger, followed by a keypad-based PIN verification derived from the package tracking number to enhance access security. A servo-controlled locking mechanism is used to physically open and close the package container, while real-time notifications and remote control are provided through a Telegram bot. The system supports two access modes: local access using voice commands and PIN input, and remote access via Telegram-based commands. System development follows a prototyping approach, and performance evaluation is conducted through functional testing, connectivity testing, and voice recognition accuracy measurements. Experimental results show that the voice recognition module achieves an average recognition accuracy of 74%, with recognition performance decreasing as the distance between the sound source and the microphone increases. Connectivity testing indicates that network latency remains within an acceptable range for distances up to 20 meters. Functional testing confirms that the locking mechanism, authentication process, and notification system operate reliably under defined test scenarios. The results demonstrate that the proposed system can serve as a practical IoT-based solution for improving package reception security and monitoring. However, the system is intended as a supportive security mechanism and does not replace advanced authentication or surveillance systems.